2020
DOI: 10.26803/ijlter.19.6.1
|View full text |Cite
|
Sign up to set email alerts
|

The Emergency Remote Learning Experience of University Students in Indonesia amidst the COVID-19 Crisis

Abstract: This study aimed to explore and interpret the lived experience of Indonesian university students in emergency remote learning (ERL) during the COVID-19. Methods of the investigation was a qualitative phenomenological approach involving 80 students from the Social Science Education Program at a public university in Jakarta. Understanding their experience was achieved through a rigorous analysis of the participants' diaries and reflective essays and an online focus group. Results revealed that the students' expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
210
1
26

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(243 citation statements)
references
References 24 publications
6
210
1
26
Order By: Relevance
“…According to Ullah, Khan, & Khan (2017) quantitative data, students indicated negative perception in understanding online learning materials without getting acquainted with appropriate guidance. Students complained about trouble finding references as the learning resources provided are limited, resulting in students gathering irrelevant information from the internet and journals (Rahiem, 2020). Lukong et al (2020) research findings showed that students preferred face-to-face learning resulting in a better understanding of online learning lessons.…”
Section: Learning Materials and Assessmentsmentioning
confidence: 99%
“…According to Ullah, Khan, & Khan (2017) quantitative data, students indicated negative perception in understanding online learning materials without getting acquainted with appropriate guidance. Students complained about trouble finding references as the learning resources provided are limited, resulting in students gathering irrelevant information from the internet and journals (Rahiem, 2020). Lukong et al (2020) research findings showed that students preferred face-to-face learning resulting in a better understanding of online learning lessons.…”
Section: Learning Materials and Assessmentsmentioning
confidence: 99%
“…This situation was certainly not ideal, but students are persistent, educators are strong-willed, and they all tried their best [20]. A mix of conventional and non-conventional methods or blended learning was utilized remotely during the COVID-19 outbreak [21]. Blended learning is the application of more than one method, strategy, technique, or media in education [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…Learning had been paradoxical during ERL; to explain how students saw learning as versatile on the one hand, but on the other, they saw it as demanding too [21]. Rahiem [21] further explained the thirteen platforms used during ERL listed by the students were: e-book/e-journals, pdf documents, YouTube videos, online meetings (Zoom, Google Meet or Microsoft Teams), WhatsApp, social media (Facebook or Instagram), Google Classroom, e-mail, Google Search Engine, Podcasts, educational websites, Audio Calls, and PowerPoint Presentations. WhatsApp was the primary tool that was used by nearly every course during the ERL period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency remote learning (ERL) is intended as a temporary shift from normal learning modes (Rahiem, 2020). The situation happens when learning becomes remote (or distant), it takes what is supposed to be face-to-face teaching and transform it to become digital education.…”
Section: Introductionmentioning
confidence: 99%